Quantitative Autofluorescence in Non-Neovascular Age Related Macular Degeneration - Shruti Chandra; Manjot K. Grewal; Sarega Gurudas; Rajan Sondh; Alan Bird; Glen Jeffery; Victor Chong; Sobha Sivaprasad (Biomedicines, 2023)
Quantitative autofluorescence (qAF8) level is a presumed surrogate marker of lipofuscin content in the retina. We investigated the changes in the qAF8 levels in non-neovascular AMD. In this prospective cohort study, Caucasians aged ≥50 years with varying severity of non-neovascular AMD in at least one eye and Snellen visual acuity ≥6/18 were recruited. The qAF8 levels were analysed in the middle eight segments of the Delori pattern (HEYEX software, Heidelberg, Germany). The AMD categories were graded using both the Beckman classification and multimodal imaging (MMI) to include the presence of subretinal drusenoid deposits (SDD). A total of 353 eyes from 231 participants were analyzed. Compared with the age-matched controls, the qAF8 values decreased in the eyes with AMD (adjusted % difference = −19.7% [95% CI −28.8%, −10.4%]; p < 0.001) and across the AMD categories, (adjusted % differences; Early, −13.1% (−24.4%, −1%), p = 0.04; intermediate AMD (iAMD), −22.9% (−32.3%, −13.1%), p < 0.001; geographic atrophy −25.2% (−38.1%, −10.4%), p = 0.002). On MMI, the qAF8 was reduced in the AMD subgroups relative to the controls, (adjusted % differences; Early, −5.8% (−18.9%, 8.3%); p = 0.40; iAMD, −26.7% (−36.2%, −15.6%); p < 0.001; SDD, −23.7% (−33.6%, −12.2%); p < 0.001; atrophy, −26.7% (−39.3%, −11.3%), p = 0.001). The qAF8 levels declined early in AMD and were not significantly different between the severity levels of non-neovascular AMD, suggesting the early and sustained loss of function of the retinal pigment epithelium in AMD.